Modelle zur Inneren Sicherheit: Neue Volkspolizisten oder Schandi zum Anfassen? Vom ABV zum KOBB - Hornbostel, Stefan; Hausmann, Christopher (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
In recent debates on inner security, there has been a clemand, not only for greater technical efficiency, but also for an increase in community-oriented behavior by the police. New models of local prevention politics and their traditions in the FRG and the GOR are discussed in this paper. The suggestion is, that despite basic differences between the two political and juridical systems, functional equivalents have emerged. Finally, the advantages and disadvantages of local prevention programmes are considered.